A Switch or a Process? Disentangling the Effects of Union Membership on Political Attitudes in Switzerland and the UK. Issue 3 (4th August 2020) - Hadziabdic, Sinisa; Baccaro, Lucio
Abstract : The paper examines the effects of union membership on individual political attitudes using panel data for Swiss and British workers. Considering union membership as an on/off switch (member vs. non‐member), as it is often done, it is only possible to distinguish between a selection effect (unions attract like‐minded individuals) and a molding effect (the experience of membership has a transformational impact on the individual). Exploiting the longitudinal structure of the data reveals that union membership is best characterized not as a switch, but as a dynamic process involving anticipation effects (which start well before becoming affiliated) and maturation effects (which become noticeable only after a certain duration of membership and may not dissipate after leaving the union). Empirically, the selection effect appears the most important in the two countries we focus on, while the molding effect is less pronounced. Anticipation and maturation effects are also non‐negligible and hitherto unexplored.